High-temperature properties and aging resistance of rock asphalt ash modified asphalt based on rutting index. (11th January 2023) - Lu, Weiwei; Peng, Xinghai; Lv, Songtao; Yang, Yi; Wang, Jinping; Wang, Ziyang; Xie, Nasi
Highlights: The rutting index difference of BRAAMA, AQRAAMA, and LPAB was analyzed. The aging resistance of BRAAMA and LPAB was evaluated. The effect of additive particle size on the high-temperature performance was studied. Abstract: Rock asphalt as a green and exceptional modifier has been successfully applied in petroleum asphalt modification, but conventional research focuses on the modification of rock asphalt as a whole. In order to reveal the rock asphalt modification effect on neat asphalt from a component angle, this paper selected the common Buton rock asphalt (BRA) and Qingchuan rock asphalt (QRA) to modify neat asphalt. Firstly, the Buton rock asphalt ash modified asphalt (BRAAMA), Qingchuan rock asphalt ash modified asphalt (QRAAMA), and limestone powder asphalt binder (LPAB) were prepared. Secondly, the temperature sweep test of three materials was performed on the high-temperature behavior. The ultraviolet (UV) aging resistance of BRAAMA and LPAB was evaluated with a rutting index ratio. Finally, the high-temperature modification effects of BRA ash and limestone powder with different particle sizes on the neat asphalt were studied, respectively. The results show that the BRA ash and QRA ash significantly improved the high-temperature performance of the neat asphalt. The modification effect of BRA ash on the neat asphalt is better than that of limestone powder in terms of high-temperature behavior and aging resistance. BRA ash particle size of 200 mesh is appropriate to modify neat asphalt. The average rutting index ratio of BRAAMA to LAPB is about eight times.